Ricardo Piglia's Plata quemada: The Queer Pietà - Herbert J Brant (Latin American Literary Review, 2020)
With the 2014 publication of Uruguayan journalist Leonardo Haberkorn’s book, _Liberaij: La verdadera historia del caso_ Plata quemada, scholars and critics must take another look at Piglia’s extraordinary 1997 novel in light of Haberkorn’s intention to reveal “the truth” of the details behind the novel’s story. This study explores the implications of Piglia’s fictionalization of the historical events, focusing specifically on the author’s decision to invent a homoerotic relationship between the two main characters —a decision that provides a key to understanding his highly complex and artistically daring version of “fake news” inspired by the events that took place in Buenos Aires and Montevideo in 1965. The invention of a queer relationship serves a powerful structural purpose in the novel. By means of this relationship, Piglia is able to join together two principle themes: his politically revolutionary message, as illustrated by the robbery and the spectacular scene when the characters burn the stolen money, and his socially revolutionary message that the love between two men can be imagined as equally emotionally intense and spiritually meaningful as the love between a man and a woman. And while the title of the novel may highlight the climactic act of rebellious socio-economic nihilism, the entire novel demands a conclusion that culminates in the radically subversive, emotionally charged image of Dorda cradling the dying Brignone, Piglia’s queer pietà.